Fikcja prawa w państwie Trzeciej Rzeszy w świetle procesu w Dreźnie przeciwko działaczom polskiego podziemia Kujawskiego Związku Polityczno-Literackiego/ Kujawskiego Stowarzyszenia Społeczno-Literackiego - Stankowski, Witold (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
The article describes the fiction of law in the Third Reich using the example of a certain trial in Dresden. The case was brought against the activists of the Polish underground movement called Kuyavian Literary-Political Association/Kuyavian Social-Literary Association. This organization was one of the first underground and pro-independence organizations in Poland at the time of the Hitlerite occupation; its reach encompassed Eastern Kuyavian region and the city of Wloclawek. It was a civil organization which did not have a military character. It had been active until the beginning of 1941 when the arrests happened. About 140 people were incarcerated; the scope of the arrests was widening as long as the Nazi investigation continued. The trial of organization’s members, which took place in Dresden in October of 1942, did not at all resemble a process of seeking justice. The proceedings were in clear violation of the rule of law. The arrests warrants were issued against arrestees after they had been locked up for almost a year in camps or prisons. Such procedure obviously infringed upon the fundamental legal principle of lex retro non agit. The conspirators’ activity was categorized as a state treason in the light of criminal law for Poles and Jews. The sentences delivered against organization’s members were extremely severe. The court ordered either the capital punishment by guillotine or imprisonment for a period of over 10 years. Prosecutors and judges simply became servile executors of recommendations issued by the totalitarian state of Adolf Hitler.
Keywords: III Rzesza; prawo; proces; Drezno (Niemcy); Kujawski Związek Polityczno-Literacki; Kujawskie Stowarzyszenie Społeczno-Literackie